IgG and IgM Serological Profile in Primary and Secondary Dengue Infection: Profil Serologis IgG dan IgM sebagai Indikator Infeksi Primer dan Sekunder Dengue - Tri Ade Saputro; Nur Vita Purwaningsih; Waras Budiman; Mulya Fitrah Juniawan (Medicra (Journal of Medical Laboratory Science/Technology), 2026)
Dengue Hemorrhagic Fever (DHF) remains a major health problem in endemic regions, requiring accurate laboratory examinations to support diagnosis. Serological testing of immunoglobulin G (IgG) and immunoglobulin M (IgM) is widely used to differentiate between primary and secondary dengue infections. This study aimed to analyze the serological profile of IgG and IgM as indicators of primary and secondary dengue infection in patients with DHF. A descriptive cross-sectional design was employed using secondary data from 170 patients who underwent IgG and IgM testing at RSUD Haji Surabaya. Data were analyzed descriptively by calculating frequency distributions and percentages. The results showed that the distribution was dominated by IgG positive and IgM negative findings (62%), followed by both IgG and IgM positive (17%), IgM positive only (10%), and both negative results (11%). These findings indicate that most patients experienced secondary dengue infection. Therefore, IgG and IgM serological testing plays an important role in determining the phase of dengue infection; however, it should be combined with other diagnostic methods to improve diagnostic accuracy.